1995
DOI: 10.1038/nm1095-1009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased salt intake on blood pressure of chimpanzees

Abstract: A colony of 26 chimpanzees given a fruit and vegetable diet of very low Na and high K intake were maintained in long-standing, socially stable small groups for three years. Half of them had salt added progressively to their diet during 20 months. This addition of salt within the human dietetic range caused a highly significant rise in systolic, mean and diastolic blood pressure. The change reversed completely by six months after cessation of salt. The effect of salt differed between chimpanzees, some having a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
202
2
10

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(220 citation statements)
references
References 37 publications
6
202
2
10
Order By: Relevance
“…[34][35][36] Studies conducted on chimpanzees showed that when exposed to high salt diets their BP levels increase, which is consistent with adaptation to a low sodium environment. 37 This evidence supports the hypothesis that modern humans inherited from their ancestors a gene that was adaptive in an environment low in sodium.…”
Section: Discussionsupporting
confidence: 79%
“…[34][35][36] Studies conducted on chimpanzees showed that when exposed to high salt diets their BP levels increase, which is consistent with adaptation to a low sodium environment. 37 This evidence supports the hypothesis that modern humans inherited from their ancestors a gene that was adaptive in an environment low in sodium.…”
Section: Discussionsupporting
confidence: 79%
“…42 Large salt losses due to sweating made sodium and water conservation essential for survival. 44 For example, humans and non-human primates from tropical climates have enhanced salt and water avidity. [25][26][27] Another consequence of this reliance on sweating is decreasing blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…21 Twenty-six chimpanzees with a mean age of 12 years (equivalent to human adolescents) were randomized into two groups: one was given their usual salt intake of approximately 0.5 g/day, which is close to humans' evolutionary intake and, in the other group, salt intake was gradually increased to 5, 10 and 15 g/day, which is similar to the current salt intake in adolescents. During the 20-month study, there was a progressive increase in the difference in blood pressure between the two groups.…”
Section: Discussionmentioning
confidence: 99%